The contribution of the nurse in monitoring the growth and development of children with Down syndrome - Zubčić, Marina (Education and Research in Health Sciences, 2023)
Introduction: Down syndrome is a chromosomal disorder, which occurs when a third copy of the whole or part of the 21st chromosome in human hereditary material is present.Objective: To consider the activities of the nurse in monitoring the growth and development of children with Down syndrome, as well as differences in progress compared to healthy peers.Method: The study group consisted of N 21 subjects, children and adolescents, with Down syndrome. The control group consisted of the same number of healthy children who met the basic criteria of matching with the study group according to gender and age. Descriptive method and indirect observation method ‒ documentation analysis were used. Documentation sheet was constructed.Results with discussion: The children with Down syndrome lag behind healthy children, more or less, in each observed segment. They are born in term, with an Apgar score in the range of 5‒10, but with smaller body weight, body length and head volume, in which they lag behind until the end of the school period. Dentition occurs later in relation to healthy children, and they also have a smaller number of teeth. They also lag behind in the development of basic mental functions. They achieve most of the milestones, but at a later age. Conclusion: Children with Down syndrome lag behind in complete psychophysical development in relation to healthy children of the same age. The nurse has a multiple role in monitoring the growth and development, and this improves the quality of the provided health services.
Keywords: Down syndrome; children; growth and development; nurse